Taking on New Challenges : A Compendium of Good Practices in Rural Water Supply Schemes - World Bank; India Ministry of Drinking Water and Sanitation (World Bank, Washington, DC, 2016)
Provision of safe drinking water is a basic necessity and has been a major topic for key political discourses in the country over the last decade. The Government of India has been focusing on safe drinking water since 1972-73 when it introduced the Accelerated Rural Water Supply Program (ARWSP) to assist States and Union Territories to accelerate the coverage of drinking water in the country. Despite increased outlays since then, access to safe drinking water in India remains a challenge. Apart from access, water quality and sustainability of resources (water points and infrastructure developed) are issues of major concern. The National Rural Drinking Water Program (NRDWP), which is supplementing the efforts of the State Governments by providing technical and financial assistance, is looking at rural drinking water from a holistic viewpoint. The Ministry has shifted its focus from hand pumps to piped water supply systems with the aim of providing monitored clean water and is focusing on those States which have low levels of piped water supply. The Water and Sanitation Program has compiled an excellent collection of success stories and best practices from the States of Kerala, Karnataka, Maharashtra, Gujarat, Jharkhand, Punjab and Uttarakhand which address these key constraints. Some of these success stories, such as the Asoga village intervention in Karnataka which showcases a unique demand driven approach to facilitate participatory decision making leading to community ownership, the Bidholi piped water supply scheme in Uttarakhand which manages and recovers 100 per cent operation and maintenance costs from the community, the Shikayat Nivaran Kendra experiment in Punjab which uses information technology for online web enabled centralised complaint redressal and the Water and Sanitation Management Organisation experiment in Gujarat where the registered body acts as a facilitator in developing water and sanitation facilities owned and managed by communities, are all outstanding examples of how to address various challenges and shortcomings the program is facing.